A Japanese case of COVID‐19: An autopsy report. Issue 10 (13th August 2020) - Okudela, Koji; Hayashi, Hiroyuki; Yoshimura, Yukihiro; Sasaki, Hiroaki; Horiuchi, Hiroshi; Miyata, Nobuyuki; Tachikawa, Natsuo; Tsuchiya, Yuki; Mitsui, Hideaki; Ohashi, Kenichi
Abstract : A 93‐year‐old woman was admitted with a 10‐day history of cough and prostration. Thoracic computed tomography revealed extensive ground‐glass opacities in both the lungs. The polymerase chain reaction test of sputum for severe acute respiratory syndrome‐coronavirus‐2 (SARS‐CoV‐2) was positive. She was treated with antiviral agents and steroid pulse therapy. However, her oxygen saturation gradually declined, and she died 10 days after hospitalization. The most important autopsy finding was fuzzily segmented diffuse alveolar damage (DAD) that expanded from the subpleural to the medial area. No remarkable changes were observed in organs other than the lungs. Therefore, pneumocytes were suggested as the primary target for SARS‐CoV‐2, which might explain why coronavirus infectious disease‐19 is a serious condition. Thus, early treatment is essential to prevent viral replication from reaching a level that triggers DAD.